2019
DOI: 10.7575/aiac.ijels.v.7n.2p.75
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of School Engagement in the Relationship between Attitude toward Learning and Academic Achievement

Abstract: The aim of the present study was to investigate the mediating role of school engagement in the relationship between attitude toward learning and academic achievement. The study was carried out on 438 high school students. The Scale of Attitudes Toward Learning and the School Engagement Scale were applied to the participants, and students' academic achievement scores were obtained from the school administration. In the study, the Pearson product-moment correlation coefficient and the ordinary least squares regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…This result may be interpreted that when family income is higher, students will be more accessible to after-school classes and get tutoring, finally they are more likely to perform well in tests. When the sense of achievement is positive, students will be more liable to participate in school activities more, they are more internally motivated toward lessons, and their academic achievement is higher(M. Yüksel Erdoğdu, 2019 [12]). Therefore, the hypothesis 2 conforms to the empirical result.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be interpreted that when family income is higher, students will be more accessible to after-school classes and get tutoring, finally they are more likely to perform well in tests. When the sense of achievement is positive, students will be more liable to participate in school activities more, they are more internally motivated toward lessons, and their academic achievement is higher(M. Yüksel Erdoğdu, 2019 [12]). Therefore, the hypothesis 2 conforms to the empirical result.…”
Section: Discussionmentioning
confidence: 99%
“…Adelabu (2007) observed that when a sense of school engagement is positive, students tend to participate more in school activities. Erdoğdu (2019) found that when the attitude towards learning is positive, individuals are more academically successful.…”
Section: Remedies To Improve Academic Performance At Islamic University Primary Schoolmentioning
confidence: 99%
“…Over the past few years, student success in chemistry and other science, technology, engineering and mathematics (STEM) fields has declined, with possible reasons being the poor perception of the field, and students' lack of engagement with these fields (Gill, 2011;PECK). It is therefore imperative that educational institutions look for ways to continue to improve engagement and retention of concepts (Erdoğdu, 2019). One of these methods has been the use of technology in the classroom (Chandran, Treagust, & Tobin, 1987;Magalhães, Ferreira, Cunha, & Rosário, 2020;Revell, 2013), which has manifested in a variety of ways, including flipped classrooms (utilizing class time for worked problems and providing online resources to replace the traditional lecture) that allow students to access the material before and after entering the lecture hall (Hibbard, Sung, & Wells, 2015;Schiller, 2013).…”
Section: Introductionmentioning
confidence: 99%